Investigation of Nasal Bone Fractures in the Framework of the Turkish Penal Code - Kafadar, Hüseyin; Kafadar, Safiye (The Bulletin of Legal Medicine, 2014)
Nasal bone fractures (lineer, deplase or distal thinner portion) is delineated in the new Turkish Penal Code (Article 87, Section 3). In the current study, we investigated the reports of injury case with nasal bone fracture and available problems in foresic medicine. Of the 2896 forensic reports of our regional Center, The Council of Forensic Medicine, 178 cases with nasal bone fractures were determined between 1 June and 31 December 2012. The cases were invetigated about age, gender, origine, type of nasal bone fracture and effect on life function. There are 178 cases in our study. Of the cases, 13,48%(24 cases) were females and 86,51% (154 cases) males, a mean age of 34 ±7. was found. Of the cases, 73.03 % (130 cases) were assault, 13.48% (24 cases) traffic accident, 10.11% (18 ceses) fall from and 3.37%(6 cases) were stab injury. Of the cases, 42.69% (76 cases) were lineer fracture, 37,07%(66 cases) were deplase fracture, 15,73%(28 cases) were fragmeted and 3,37% (6 cases) were distal thinner portion fracture. Becauseofalltraumaticnasalinjuries areconsidered judicial cases that whith the goal of determination types of nasal bone fracture, x-Ray wiew and computerized tomography should investigate. We have considered that if it is clearly writen type of nasal bone fracture in foresic reports, recurrent correspondence would not have and judiciary process would not extend. Key words: Forensic medicine, nasal fracture, trauma.